Effect of non-pharmacological interventions on anxiety, depression, sleep quality, and pain after orthopedic surgery: A protocol for systematic review and network meta-analysis. Issue 44 (5th November 2021) - Zhang, Xingquan; Zhou, Genxin; Chen, Naifei; Zhang, Yonghua; Gu, Zenghui
Abstract: Background: Patients after orthopedic surgery often experience the pain, anxiety, depression, and sleep disturbances, which can be greatly reduced by non-pharmacologic interventions as alternative therapies. Randomized controlled trials of nonpharmacologic interventions for anxiety, depression, sleep quality, and pain in patients after orthopedic surgery have been reported, but the results may be conflicting. Evidence to determine the optimal non-pharmacological intervention with a high efficacy is limited. This study aims to assess the effects of non-pharmacologic interventions on the bone anxiety, depression, sleep quality, and pain in patients after orthopedic surgery through a network meta-analysis, thus providing guidance in clinical application. Methods: A systematic search of randomized controlled trials reporting the effects of non-pharmacological interventions on anxiety, depression, sleep quality and pain after orthopedic surgery published before October 2021 will be searched in Wanfang, VIP Information Chinese Journal Service Platform, China National Knowledge Infrastructure, Chinese BioMedicine Literature Database, Pubmed, Embase, Cochrane, and Web of science. Two reviewers will be independently responsible for study selection, quality appraisal, and data extraction. Stata 14.0 software will be used to perform the network meta-analysis. Results: The findings of this research will be reported in a recognized journal. Conclusion: This meta-analysis will provide the stronger evidence for non-pharmacological interventions on alleviating bone anxiety, depression, sleep quality, and pain in patients after orthopedic surgery, which will help clinicians and decision makers in their choices. Open Science Framework registration number: DOI 10.17605/OSF.IO/2SCBD.